A Low-Complexity MIMO-OFDM Transmission Scheme for Optical Wireless Communications - Wei-Wen Hu (IEEE Access)
A novel low-complexity multiple-input multiple-output orthogonal frequency division multiplexing transmission scheme for optical wireless communications (OWC), referred to as LC-MIMO-OFDM, is introduced in this paper. LC-MIMO-OFDM eliminates the need for inverse fast Fourier transform or inverse fast Hartley transform operations at the transmitter, resulting in the reduced computational complexity in generating unipolar transmission signals. In LC-MIMO-OFDM, the modulated symbols first undergo a phase rotation operation, followed by separate extraction of their real and imaginary components. These components are then converted into positive signals by adding a direct current bias. Finally, LC-MIMO-OFDM uses two light-emitting diodes to transmit positive signals via the OWC channel. Comparative analysis shows that the LC-MIMO-OFDM offers better peak-to-average power ratio reduction than do existing unipolar transmission schemes for MIMO-OFDM OWC systems while maintaining lower complexity. Additionally, the proposed scheme outperforms well-known unipolar MIMO-OFDM OWC systems operating at the same spectral efficiency in terms of the bit error rate.